Experimental Investigation of Operational Behaviour of Elastomeric Center-Coupler Draft Gear - B. G. Keglin; M. G. Voinovskiy; A. P. Boldyrev (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
The paper tackles functioning aspects of elastomeric center-coupler draft gears. For the time being such draft gears are the only shock absorbers responsible for safe and secure transportation of hazardous materials and high-value car-goes. The predecessor research works dealing with force pattern intrinsic to impact and compression failed to present the clean-cut description of pressure field structure within the draft gear chambers, thus making difficult mathematical modeling of such a complicated device. The authors of the described research managed to fill the indicated gap through use of up-to-date high-quality sensors capable of tracing pressure values up to 300 MPa. The center-coupler draft gear EPA-110 with crucial component in the form of double-chamber plunger assembly with a partition piston group was selected as a full-scale object of research. There are presented outcomes produced by experimental research and computations of the pressure values in the draft gear chambers in terms of different patterns of orifice holes used for quasi-static and dynamic testing. Also there are introduced new dependences to be used in calculations of force acting upon the draft gear and are provided rec-ommendations concerning introduction of amendments to the draft gear design and modification of its mathematical model.